Synthesis and Cytotoxic and Antiviral Profiling of Pyrrolo- and Furo-Fused 7-Deazapurine Ribonucleosides - Tokarenko, Anna; Lišková, Barbora; Smoleń, Sabina; Táborská, Natálie; Tichý, Michal; Gurská, Soňa; Perlíková, Pavla; Frydrych, Ivo; Tloušt'ová, Eva; Znojek, Pawel; Mertlíková-Kaiserová, Helena; Poštová Slavětínská, Lenka; et al. (Journal of medicinal chemistry, 2018)
Three series of isomeric pyrrolo- and furo-fused 7-deazapurine ribonucleosides were synthesized and screened for cytostatic and antiviral activity. The synthesis was based on heterocyclizations of hetaryl-azidopyrimidines to form the tricyclic heterocyclic bases, followed by glycosylation and final derivatizations through cross-coupling reactions or nucleophilic substitutions. The pyrrolo[2',3':4,5]pyrrolo[2,3- d]pyrimidine and furo[2',3':4,5]pyrrolo[2,3- d]pyrimidine ribonucleosides were found to be potent cytostatics, whereas the isomeric pyrrolo[3',2',4,5]pyrrolo[2,3- d]pyrimidine nucleosides were inactive. The most active were the methyl, methoxy, and methylsulfanyl derivatives exerting submicromolar cytostatic effects and good selectivity toward cancer cells. We have shown that the nucleosides are activated by intracellular phosphorylation and the nucleotides get incorporated to both RNA and DNA, where they cause DNA damage. They represent a new type of promising candidates for preclinical development toward antitumor agents.
Keywords: Antiviral Agents; Cell Line, Tumor; antivirové látky; techniky syntetické chemie; puriny; Furans; Structure-Activity Relationship; lidé; Antineoplastic Agents; protinádorové látky; Chemistry Techniques, Synthetic; furany; ribonukleosidy; Pyrroles; Ribonucleosides; Purines; vztahy mezi strukturou a aktivitou; pyrroly; nádorové buněčné linie; Humans